(untitled) (International journal of artificial intelligence, 2025)
This article highlights the achievements made in the field of sports in Uzbekistan in recent years and their social and international significance. It discusses the results achieved by national athletes in international competitions, the development of sports infrastructure, and the growing popularity of sports among young people. Furthermore, the article analyzes the role of sports achievements in promoting a healthy lifestyle in society and demonstrates the increasing prestige of Uzbek sports on the global stage.